Ritual imagination : a study of tromba possession among the Betsimisaraka in eastern Madagascar - Nielssen, Hilde. (Studies of Religion in Africa, 2012)
Ritual Imagination is a study of spirit possession and ritual dynamics. Based on fieldwork in eastern Madagascar, Hilde Nielssen shows how tromba possession works as a flexible and fluid force, whose ritual imaginary playfully draws together elements from radically different cultural and social domains, thereby constituting human realities and creating ways of relating to changing and disjunctive circumstances. Tromba's strength lies in its fluid capacities to relate to ongoing social change by altering its own practices, while at the same time continuing to heal person and cosmos. The book critically addresses the still dominant perspective in anthropology, where rituals are understood as representations of culture and society. Using tromba as a pivotal case in the critique of ritual as representation, this book offers a fresh perspective on ritual and spirit possession.